Climate‐Driven Stratification Intensifies Internal Wave Cooling on a Shallow Island Reef - Justin S. Rogers; Shuwen Tan; Kristen A. Davis; Geno Pawlak; Oliver B. Fringer (Geophysical Research Letters, 2025)
Abstract As ocean temperatures rise, understanding the cooling role of internal waves is crucial for reef preservation. Climate‐induced surface warming increases stratification, altering internal wave propagation. We use high‐resolution, nonhydrostatic simulations at Dongsha Atoll in the South China Sea to explore seasonal bottom temperature changes affecting benthic ecosystems for climate scenario SSP5‐8.5 for 2020 and 2100. Our findings show internal waves transport cooler, deeper waters into shallow areas, reducing warming by up to 2.3°C relative to conditions without waves. Enhanced stratification and internal tide forcing in a warmer, more strongly stratified ocean increases wave‐driven cooling by up to 0.5°C in shallow zones. Variability in bottom temperature are also enhanced by up to 4.5°C. However, net warming by 2100 is projected at up to 2.8°C in shallow areas and 0.9°C in deeper regions. Areas with strong internal wave activity could serve as thermal refugia, despite overall trends pointing to continued ocean warming.